2014
DOI: 10.1007/s00392-014-0804-1
|View full text |Cite
|
Sign up to set email alerts
|

Oral anticoagulation is frequently discontinued after ablation of paroxysmal atrial fibrillation despite previous stroke: data from the German Ablation Registry

Abstract: Even in patients with previous stroke, OAC was frequently discontinued during FU after PAF ablation in this observational study. However, TE occurred significantly more frequent in these high-risk patients. These data argue against OAC discontinuation after ablation in patients with previous stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 20 publications
1
30
1
Order By: Relevance
“…Numerous investigators have also reported a strong association between advanced age, prior stroke/TIA, high CHADS2, CHA2DS2-VASc, and HAS-BLED scores, and stroke/TIA and major bleeding. [9][10][11][12]20,21 Although some recent studies have shown a significant association between AF recurrence and stroke/TIA events, 22 our study did not. We cannot say with certainty that AF did not recur asymp-continued when, even after AF, the CHA2DS2-VASc score is ≥2.…”
Section: Discussioncontrasting
confidence: 68%
“…Numerous investigators have also reported a strong association between advanced age, prior stroke/TIA, high CHADS2, CHA2DS2-VASc, and HAS-BLED scores, and stroke/TIA and major bleeding. [9][10][11][12]20,21 Although some recent studies have shown a significant association between AF recurrence and stroke/TIA events, 22 our study did not. We cannot say with certainty that AF did not recur asymp-continued when, even after AF, the CHA2DS2-VASc score is ≥2.…”
Section: Discussioncontrasting
confidence: 68%
“…In a German Ablation Registry observational study, Nuhrich et al 46 have reported that TE occurred more often in the high-risk group This meta-analysis did not identify significant differences in TE between two groups (on-OACs and off-OACs group, Figure 2), which may indicate the feasibility of OACs withdrawal 3 months after successful RFCA for AF. Nevertheless, we detected mild heterogeneity, and consequently preformed subgroup analysis.…”
Section: Discussionmentioning
confidence: 73%
“…They concluded that continuing OACs indefinitely in high‐risk patients is the safest strategy. In a German Ablation Registry observational study, Nuhrich et al . have reported that TE occurred more often in the high‐risk group (previous stroke) than in the low‐risk group (no previous stroke) (4.3% vs 0.3%, P < 0.05) during a median follow‐up of 489 days.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent reason for discontinuation of anticoagulation treatment in our registry was permanent return to sinus rhythm. This group of patients is perceived as a low-risk group and especially after successful ablation treatment, anticoagulation treatment is oftentimes discontinued in clinical practice [20]. There is, however, no evidence supporting a discontinuation of anticoagulation in patients reporting a permanent return to sinus rhythm, because AF may be asymptomatic in nature.…”
Section: Discussionmentioning
confidence: 99%